Exercise-induced arterial hypoxaemia in athletes: a review - Prefaut, C.; Durand, F.; Mucci, P.; Caillaud, C. (Sports Medicine, 2000)
During exercise, healthy individuals are able to maintain arterial oxygenation, whereas highly-trained endurance athletes may exhibit an exercise-induced arterial hypoxaemia (EIAH) that seems to reflect a gas exchange abnormality. The effects of EIAH are currently debated, and different hypotheses have been proposed to explain its pathophysiology. For moderate exercise, it appears that a relative hypoventilation induced by endurance training is involved. For high-intensity exercise, ventilation/perfusion (V(A)/Q) mismatching and/or diffusion limitation are thought to occur. The causes of this diffusion limitation are still under debate, with hypotheses being capillary blood volume changes and interstitial pulmonary oedema. Moreover, histamine is released during exercise in individuals exhibiting EIAH, and questions persist as to its relationship with EIAH and its contribution to interstitial pulmonary oedema. Further investigations are needed to better understand the mechanisms involved and to determine the long term consequences of repetitive hypoxaemia in highly trained endurance athletes.